SISTEM INFORMASI PEMBAYARAN KOMPONEN PENDIDIKAN BERBASIS WEBSITE PADA STMIK BUMIGORA MATARAM - Irfan, Pahrul; Mardedi, Lalu Zazuli Azhar (ILKOM Jurnal Ilmiah, 2018)
STMIK Bumigora is the first college in West Nusa Tenggara that has an informatics engineering department. One of the problems faced by STMIK Bumigora is the absence of an online payment information system. The payment process that runs at this time is a conventional model that is through bank transfers that previously had to take a payment slip to the finance department, this process is of course not effective and efficient because it takes not a little time. From these problems, it is necessary to develop applications that can help the process of paying for tuition costs online. The system is developed using the waterfall method where there are several processes, namely the need for analysis, system design, implementation, testing, and maintenance. The results obtained from this study are an application for payment of the education cost component that can help students and institutions of higher education in the process of paying for education costs at STMIK Bumigora Mataram.